GBT e prisões: uma análise criminológico-queer do cárcere pernambucano. - Morais, Neon Bruno Doering (2018)
The purpose of this current dissertation is to analyze housing and GBT population conditions in the prison of Pernambuco for the purpose of refining the lens supplied by the critical criminology and bring to the scene experiences of transvestites and gays in prision until now unrecognized in criminological studies. It has as initial assumptions for this analysis that the Criminal Justice System remains incipient in relation to the effects of heteronormative culture. The prisons marked by sexual dimorphism remain in time as punitive institutions separated by sex: “male” and “female” prisons. However, recently in Brazil were implemented the first specific living spaces for the GBT population in male prisons, and in 2014 was inaugurated the Pavilion without Prejudice in the Igarassu Prison (PIG). But this is not the reality of many, transvestites and gays continue to suffer violence, more often and markedly. In this job, a multisited field exploratory survey was carried out, built on several fronts of analysis, and interviews with arrested transvestites and gays in the PIG, located in the Metropolitan Region of Recife, as the main source. The interviews revealed that despite the conditions are still bad, the reserve for GBT wings/pavilions represents a significant gain. However, the maintenance and organization of these spaces still depend on many aspects of the discretion of prison management. The decision of who will or will not go there, depends on personalized decisions, often the “locksmith” is who does the capture. It was observed that the prison environment reflects male domination, since people with “feminine” behaviors, feel more difficult in fulfilling their sentences, not to mention the difficult relations between themselves. Among the reports collected from the internees, for example, are rape, servitude and homophobia of the officials prision. This work, proposes a dialogue between critical criminology and queer theories for training of this recent subversive direction called queer criminology, which, combined with the gains conquered by feminist criminology, expands the horizons of criminological studies (beyond the traditional class clipping) by introducing gender and sexuality markers. Such formulations help to problematize jail logic racist, homophobic, misogynous and androcentric logic, that punishes and inflicts pain and suffering. The magnification of the criminology landscape makes the focus of critical criminology shifting to the notion of abjection, which helps in understanding of other dynamics power. The data of this research show that much has to be done to subvert the persistent reality of violence against GBT in prision.